An evaluation of Access to Psychological Services Ireland: year one outcomes. (6th November 2015) - McHugh, P.; Martin, N.; Hennessy, M.; Collins, P.; Byrne, M.
Abstract : Objectives: To evaluate the clinical effectiveness and cost-effectiveness of Access to Psychological Services Ireland (APSI), a primary care adult psychology service. Methods: A repeated measures design was used to evaluate the clinical outcomes of service users who completed an intervention. Psychological distress, depressive symptomatology and anxiety symptomatology were measured using the Clinical Outcomes in Routine Evaluation–Outcome Measure (CORE-OM), the Patient Health Questionnaire-9 (PHQ-9) and the Generalised Anxiety Disorder-7 (GAD-7), respectively. Self-reported health and economic outcomes were measured using the EQ-5D-3L and the Eco-Psy, respectively. Results: A total of 381 adults were assessed as suitable for an APSI intervention, with 198 (52%) of these completing at least one intervention. Significant reductions in psychological distress were observed for completers of guided self-help and brief cognitive behavioural therapy, with service users also showing significant reductions in anxiety and depressive symptomatology. Reliable and clinically significant change on the CORE-OM was observed for 67.9% of treatment completers. Service users reported significant improvements in their health status but did not show changes in their health service usage in the 3-month follow-up period. Conclusions: APSI provided an accessible service model that was clinically effective in managing a range of mild to moderate mental health difficulties. The cost-effectiveness of the service model may be enhanced by offering a wider range of high-throughput interventions and by increasing the treatment completion rate.